2013
DOI: 10.3855/jidc.2801
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal candidiasis and Candida colonization in HIV positive patients in northern India

Abstract: Introduction: Oropharyngeal candidiasis (OPC) is the most common opportunistic fungal infection reported in human immunodeficiency virus (HIV) positive patients worldwide. This prospective study was undertaken to investigate OPC and Candida colonization (CC) and their correlation with CD4+ cell counts and antiretroviral therapy (ART) in HIV-positive patients. Methodology: In total, 190 HIV-positive patients were enrolled for study in three groups as follows: Group A, 90 patients without ART; Group B, 100 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 21 publications
10
38
1
Order By: Relevance
“…Regarding C. albicans proportion within the HIV isolates, values similar to the one in this study (70%) have been reported for Taiwan (Ho et al, 2014), Cameroun (dos Santos Abrantes et al, 2014), USA (Merenstein et al, 2013), Spain (Ramírez et al, 2006) or Turkey (Erköse and Erturan, 2007). Percentages can go as high as 90% in India (Maurya et al, 2013), Italy (Giammanco et al, 2002) or UK (Cartledge et al, 1999), 83% in South Africa (dos Santos Abrantes et al, 2014), 79% in Serbia (Mitrovic et al, 1996), or can go as low as 62% in Turkey (Erköse and Erturan, 2007) or Brazil (Costa et al, 2006). Again, C. glabrata is missing from the isolates in our non-albicans Candida group.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Imentioning
confidence: 99%
“…Regarding C. albicans proportion within the HIV isolates, values similar to the one in this study (70%) have been reported for Taiwan (Ho et al, 2014), Cameroun (dos Santos Abrantes et al, 2014), USA (Merenstein et al, 2013), Spain (Ramírez et al, 2006) or Turkey (Erköse and Erturan, 2007). Percentages can go as high as 90% in India (Maurya et al, 2013), Italy (Giammanco et al, 2002) or UK (Cartledge et al, 1999), 83% in South Africa (dos Santos Abrantes et al, 2014), 79% in Serbia (Mitrovic et al, 1996), or can go as low as 62% in Turkey (Erköse and Erturan, 2007) or Brazil (Costa et al, 2006). Again, C. glabrata is missing from the isolates in our non-albicans Candida group.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Imentioning
confidence: 99%
“…candidemia). OPC is an indicator of the development of acquired immune deficiency syndrome (AIDS) and depending on the stage of the infection by human immunodeficiency virus (HIV), about 90% of the patients have OPC [3,4]. Candida albicans is the most prevalent species related to this infection [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 90% of HIV-AIDS patients is exposed to oral Candidiasis during the progression of the disease, so the infection is closely related to HIV infection. 1,5 In many countries that have not been able to distribute Highly Active Anti-Retroviral Therapy (HAART) evenly, such as in Indonesia, mucosal candidiasis is still the highest cause of morbidity in AIDS patients. 5,13 Sabouraud broth and dextrose agar media were used as media for Candida growth in this research.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 In many countries that have not been able to distribute Highly Active Anti-Retroviral Therapy (HAART) evenly, such as in Indonesia, mucosal candidiasis is still the highest cause of morbidity in AIDS patients. 5,13 Sabouraud broth and dextrose agar media were used as media for Candida growth in this research. These media have acidic concentration (pH 5.6), so the growth of bacteria that are not acid resistant will be inhibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation